An Assessment of People with Intellectual Disabilities Practicing of Physical Activities and Its Challenges under Corona Pandemic (Covid-19) from Their Families' Point of View (Journal Of Educational and Psychological Researches, 2023)
AbstractThis research aims to assess the practice of physical activities by people with intellectual disabilities and its challenges during the Coronavirus (COVID-19) pandemic from their families' point of view. The research sample consisted of (87) individuals from families with intellectual disabilities in the Makkah region. The sample was selected by the simple random method where the researcher used the descriptive analytical approach. A questionnaire of (32) items was used as the research tool to collect data. The findings of the study showed that the assessment level of practicing physical activities by people with intellectual disabilities was low. The public facilities dimension ranked first with a moderate degree followed by clubs and sports centers in the second rank with a low degree. The house dimension came in the third rank with a low degree of utilization. The challenges of practicing physical activities by people with intellectual disabilities came to a moderate degree. The findings also revealed that there is a statistically significant difference at (α = 0.05) for people with intellectual disabilities in their practice of physical activities. Furthermore, the findings showed statistically significant differences in challenges at (α = 0.05) for practicing physical activities during the COVID-19 pandemic from their families’ point of view